Promote Foreign Direct investment in the Federal Companies Law No. (32) of 2021 AD - Al-Mulla, Sheikh; Hattab, Rasha (Journal of Legal Sciences, 2026)
UAE "is one of the countries seeking to attract foreign direct investment" by modernizing of its legal and physical infrastructure. Additionally, it pushed the private sector to form partnerships with foreign companies, particularly multinational companies, and it signed numerous bilateral and group agreements with numerous countries and trading partners. the passing of Federal Law No. 34 of 2021 AD, which dealt with commercial countries, gave numerous incentives and guarantees "to increase the flow of foreign direct investment into the" UAE. By studying the investment climate in the UAE, and the adequacy of incentives and legislative guarantees that it provides for foreign direct investment, the study aimed to determine the adequacy of incentives and guarantees for foreign direct investment in UAE. "the study came to a number of conclusions", most notably, that incentives and guarantees, "by creating an environment that is conducive to" investing and enacting regulations that are both encouraging and alluring, are the key to safety and confidence for investors. the study concluded with several recommendations, including: reinstatement of "the investment law and" removing "the obstacles represented by the current law, the most important of which are granting incentives, privileges and facilities", and "working according to the concept of" a "single window. the "establishment of specialized courts to handle disputes related to cases and the speed of separation of adversaries, and that the rulings of these courts are enforceable and not subject to appeal.